Identification and exclusion of intermediates of photocatalytic CO2 reduction on TiO2 under conditions of highest purity. Issue 16 (14th March 2016) - Pougin, Anna; Dilla, Martin; Strunk, Jennifer
Abstract : On TiO2 P25, CO is not an intermediate in photocatalytic CO2 reduction; instead, a mechanism involving C2 intermediates is likely. Abstract : Using a high-purity gas phase photoreactor and highly sensitive trace gas analysis, new insights into the mechanism of photocatalytic CO2 reduction on TiO2 P25 have been obtained. The reactor design and sample pretreatment excludes product formation from intermediates. Apart from CO2, the only other reactant offered to the catalyst is water. The main products found on this prominent photocatalyst are methane and carbon monoxide. To distinguish between the three possible mechanisms reported in previous studies, likely intermediates of the reaction were added to the TiO2 photocatalyst and their reactivity was followed by gas chromatographic analysis. Based on the results, we can clearly rule out CO as intermediate of any photocatalytic reaction pathway on TiO2, because CO was not converted at all within a course of six hours. An improvement of carbonate formation on TiO2 brought about by surface-doping with sodium decreased product yields, so carbonates are unlikely intermediates as well. Methanol, formaldehyde and formic acid were exclusively oxidized back to CO2 . We thus support a mechanism running over C2 -intermediates, and we tested our hypothesis by reacting glyoxal, glyoxylic acid, acetic acid and acetaldehyde on TiO2 . The reactions of acetaldehyde and acetic acid led to product distributions very similar to those obtained from CO2 under the standard reaction conditions, strongly supporting the C2 mechanism. This mechanism can also explain the small amounts of ethane usually found in the product mixture.